A Lossless Layered-Based Non-Encoding Plain Text Compression and Encryption Algorithm Utilizing Binary Fragmentation and Defragmentation Technique - Mishra, Pratham; Pathak, Sunil; Singh, Bhupesh Kumar; Katara, Mayuree; Kumar, Gireesh (IEEE access, 2025)
This paper proposes an innovative fusion of encryption and compression techniques that optimizes data handling and security. The approach employs a layered non-encoding encryption-compression algorithm DQRc (Data in Quick Response Code) that attempts to redefine data compression with layer-by-layer key-based encryption. This paper marks a transformative milestone in data optimization and protection, it offers a solution that not only efficiently compresses data but also safeguards it with robust encryption. In comparative analyses with convectional encryption-compression algorithms, the proposed method demonstrates significant improvements across several key performance indicators. he DQRc algorithm notably reduces processing times, achieving faster encryption and decryption cycles which is essential for time-sensitive applications. Furthermore, its design ensures completely lossless decompression, thereby delivering 100% data accuracy-a critical enhancement over existing methods that sometimes incur minor data losses. In terms of compression efficiency, the algorithm excels by achieving a higher compression percentage, measured by the absolute difference between the actual file size and the compressed size. This superior compression capability enables more effective storage utilization and faster data transmission without compromising the integrity of the original information. Overall, the DQRc algorithm represents a significant advancement in secure data management, providing an optimal blend of speed, accuracy, and compression efficiency.